FAIR SETTLEMENT RECONSTRUCTION OF PROBLEMATIC CREDIT DISPUTE AT BANK RAKYAT INDONESIA (STUDY CASE AT MEDANSINGAMANGARAJA BRI BRANCH OFFICE) - Bachtiar Simatupang; Jelly Leviza (The 2nd Proceeding “Indonesia Clean of Corruption in 2020", 2020)
The role of banking in the economy as the intermediary institution will strengthen the economic structure of a country. Loans extended by the bank to borrowers have risks to be stuck credit such as experienced by banking institutions including Medan Singamangaraja BRI Branch Office. Therefore, the problems in this study are about causes of stuck credit, efforts of the bank business in the implementation of dispute resolution over stuck and problematic credits and the ways of reconstruction of problematic credit dispute at Medan Singamangaraja BRI Branch Office. This research is descriptive empirical jurisdiction, and the research results show that the causes of stuck credit at Medan Singamangaraja BRI Branch Office are due to internal factors (weakness in credit analysis and credit documents, as well as carelessness of bank officer), and external factors (economic and political situation, in the country, and Legal Policy of the Government). Efforts of Medan Singamangaraja BRI Branch Office to anticipate stuck credit are preventively applying the precautionary principle (Prudential Principle) in credit distribution procedures, and repressively through Restructuring, sale of security object of credit under hand, and if the efforts do not yield results, then lines to resolution at courts are chosen, through the State Receivables Affairs Committee. From the results of fair dispute resolution of stuck credit, the reconstructions are as follows: 1. Article 2 of Law No. 7 of 1992 states: "Bank Indonesia in running the banking business is based on economic democracy using the precautionary principle; providing criminal and administrative sanctions to employees who violate the principles of prudence, resulting in stuck credit and causing losses for banks/state 2. To achieve equitable settlement credit dispute, then in the letter of credit agreement a firm clause must be included, that: "In the event of disagreement or dispute settlement of stuck credit occurring between the bank / creditor and the debtor, the parties concerned will choose the best dispute resolution for them through banking mediation, and if they fail, they will take the path of litigation or referral to the State Receivables Affairs Committee " Keywords: Bank, Stuck Credit, Justice Value